Kožna tiha perioda - določitev normativnih vrednosti - Peterlin-Potisk, Karmen (Rehabilitacija (Ljubljana), 2012)
Introduction: The cutaneous silent period (CSP) is a transient suppression of electromyographic voluntary isometric activity that follows painful electrical stimulation of cutaneous nerves. Standard electromyographic equipment is used for recording the CSP. The values of CSP in the literature vary due to different methods used by investigators. The aim of our study was to establish normal values of CSP and to compare these values to those in the literature. Methods: Mean values and standard deviations of temporal parameters of CSP (onset latency, endpoint and duration of CSP) during voluntary isometric muscle contraction that follows painful electrical stimulation (ES) of cutaneous nerves of the right upper and lower limb were established in 30 healthy volunteers. CSP was recorded from abductor pollicis brevis muscle (APB) after ES of cutaneous nerves on index and little finger; from extensor digitorum communis muscle (EDC) after ES of superficial radial nerve, and from tibialis anterior muscle (TA) after ES of sural nerve. Results: Mean value and standard deviation ( SD) of CSP onset latency detected over APB were 70.9 9.3 ms, duration 55.1 10.0 ms, endpoint 125.5 11.1 ms after ES of cutaneous nerve on index finger, and 71.8 9.0 ms, duration 52.2 8.9 ms, endpoint 123.7 10.1 ms after ES of cutaneous nerve on little finger. CSP onset latency detected over EDC after ES of superficial radial nerve was 63.5 6.3 ms, duration 44.4 5.7 ms, endpoint 107.9 8.5 ms; the CSP onset latency detected over TA after ES of sural nerve was 97.1 8.7 ms, duration 68.1 11.0 ms, endpoint 165.4 12.0 ms. Conclusion: CSP is a simple electromyographic method that can be useful in demonstrating dysfunction of thin slow conducting nerve fibres and cutaneous nociceptive mechanisms in spinal cord lesions. We established normal values of temporal parameters of CSP in healthy volunteers to enable a more accurate assessment of the small diameter A-delta nerve fibres and spinal inhibitory mechanisms in patients.
Keywords: A-delta fibres; cutaneous silent period; diagnostične metode; elektromiografija; hotena mišična kontrakcija; jakost dražljaja; kožna tiha perioda; stimulus intensity; vlakna A-delta; voluntary muscle contraction